Incidence of limb fracture across Europe: results from the European Prospective Osteoporosis Study (EPOS). - Ismail, A; Pye, SR; Cockerill, W; Lunt, M; Silman, A; Reeve, J; Banzer, D; Benevolenskaya, L; Bhalla, A; Bruges Armas, J; Cannata, J; Cooper, C; et al. (2002)
The aim of this population-based prospective study was to determine the incidence of limb fracture by site and gender in different regions of Europe. Men and women aged 50-79 years were recruited from population registers in 31 European centers. Subjects were invited to attend for an interviewer-administered questionnaire and lateral spinal radiographs. Subjects were subsequently followed up using an annual postal questionnaire which included questions concerning the occurrence of new fractures. Self-reported fractures were confirmed where possible by radiograph, attending physician or subject interview. There were 6451 men and 6936 women followed for a median of 3.0 years. During this time there were 140 incident limb fractures in men and 391 in women. The age-adjusted incidence of any limb fracture was 7.3/1000 person-years [pyrs] in men and 19 per 1000 pyrs in women, equivalent to a 2.5 times excess in women. Among women, the incidence of hip, humerus and distal forearm fracture, though not 'other' limb fracture, increased with age, while in men only the incidence of hip and humerus fracture increased with age. Among women, there was evidence of significant variation in the occurrence of hip, distal forearm and humerus fractures across Europe, with incidence rates higher in Scandinavia than in other European regions, though for distal forearm fracture the incidence in east Europe was similar to that observed in Scandinavia. Among men, there was no evidence of significant geographic variation in the occurrence of these fractures. This is the first large population-based study to characterize the incidence of limb fracture in men and women over 50 years of age across Europe. There are substantial differences in the descriptive epidemiology of limb fracture by region and gender.